Seed dispersal networks in the Galapagos and the consequences of alien plant invasions - Heleno, Ruben (2012)
Alien plants are a growing threat to the Galápagos unique biota. We evaluated the impact of alien plants on eight seed dispersal networks from two islands of the archipelago. Nearly 10 000 intact seeds from 58 species were recovered from the droppings of 18 bird and reptile dispersers. The most dispersed invaders were Lantana camara, Rubus niveus and Psidium guajava, the latter two likely benefiting from an asynchronous fruit production with most native plants, which facilitate their consumption and spread. Lava lizards dispersed the seeds of 27 species, being the most important dispersers, followed by small ground finch, two mockingbirds, the giant tortoise and two insectivorous birds. Most animals dispersed alien seeds, but these formed a relatively small proportion of the interactions. Nevertheless, the integration of aliens was higher in the island that has been invaded for longest, suggesting a time-lag between alien plant introductions and their impacts on seed dispersal networks. Alien plants become more specialized with advancing invasion, favouring more simplified plant and disperser communities. However, only habitat type significantly affected the overall network structure. Alien plants were dispersed via two pathways: dry-fruited plants were preferentially dispersed by finches, while fleshy fruited species were mostly dispersed by other birds and reptiles.